Scaling Considerations for Organic Photovoltaics for Indoor Applications. Issue 7 (14th May 2022) - Burwell, Gregory; Sandberg, Oskar J.; Li, Wei; Meredith, Paul; Carnie, Matt; Armin, Ardalan
Abstract : Organic semiconductor‐based photovoltaic (OPV) devices have many properties that make them attractive for indoor applications, such as tailorable light absorption, low embodied energy manufacturing and cost, structural conformality, and low material toxicity. Compared to their use as organic solar cells (OSCs) for standard outdoor solar harvesting, indoor OPV (IOPV) devices operate at low light intensities, and thus demonstrate different area‐scaling behavior. In particular, it appears as though the performance of large‐area IOPV devices is much less affected by the sheet resistances of the transparent conductive electrodes (a major limit in OSCs), but instead by factors such as their shunt resistance at low light intensities. Herein, the key parameters for improving the efficiency of large‐area IOPV using drift–diffusion and finite element modeling (FEM) are examined. The scaling behavior at low‐light intensities is theoretically and experimentally probed and demonstrated using the model PM6:Y6 system. The implications for the fabrication of large‐area devices and the requirements for high shunt resistances for low‐light performance are examined. These new insights present a clear route toward realizing monolithic large‐area organic photovoltaic cells for indoor applications – which is a necessary technical step to practical implementation. Abstract : Owing to properties such as tailorable light absorption, solution processability, and low material toxicity, organic photovoltaic (OPV) devices are particularly suited to indoor light‐harvesting applications. Such devices may be used incorporated into sensor devices for "Internet‐of‐Things" (IoT) applications. Herein, the implications for the fabrication of large‐area devices and the requirements for large shunt resistances for low‐light performance are examined.